Experimental Study of the Influence of Excavation Surface Stability and Sand Flowability Caused by Dense Slurry–Earth Pressure Balance Shield Tunneling in Silty Sand Stratum. (25th August 2020) - Qian, Yongjin; Min, Fanlu; Mo, Zhenze; Fan, Xihui
Abstract : Silty sand is highly permeable and has a large internal friction angle. To ensure the stable and efficient construction of the Earth pressure balance (EPB) shield in silt stratum, it is necessary to reduce the disturbance to the stratum during tunneling and reduce the risk of spewing and blocking during soil discharge. Thus, a new type of dense slurry-EPB shield construction technology is proposed. Using a custom-made test device, the consolidation tests were conducted on sand after mixing it with different amounts of slurry to study the change in the pore pressure in the mixed soil and sand stratum and analyze the stress transmission rule. In addition, slump tests were conducted on the mixed soil to study the change in the fluidity. Based on the laboratory test results, a field investigation was carried out to study the effects of the amount of slurry addition on the pore pressure in the stratum, the driving parameters, and the sand's flowability during shield tunneling. The results show that when the amount of slurry reaches a certain value, the filter cake effect occurs. The greater the amount of slurry added during the shield tunneling, the smaller the rate of change of the pore pressure in the stratum. When the amount of BC2 slurry added reached 8 m 3 per ring, the rate of change was reduced by 57%, and the slump value improved by 93%. The type of filter cake of the DS-EPB shield was only internal filter cake during tunneling, which reduced the disturbance of the excavation face and improved the flowability of the sand. These results are of great significance to the application and promotion of DS-EPB shields in sandy cobble strata.